PENGARUH KOMBINASI EKSTRAK BIJI MAHONI DAN BATANG BROTOWALI TERHADAP MORTALITAS DAN AKTIVITAS MAKAN ULAT GRAYAK PADA TANAMAN CABAI RAWIT - EKA SEPTIAN, RODHIYAH Eka (Universitas Negeri Surabaya, 2013)
Armyworm (Spodoptera litura) is one pest for crops cayenne. Yield losses due to pests has reached 40%. Pest control armyworms can be made using plant-based insecticide that is of mahogany seeds and stems brotowali. The purpose of this study was to describe the effect of the combination of mahogany seed extract and stem brotowali on mortality and feeding activity armyworm pests in pepper sauce, and determine the concentration of a combination of mahogany seed extract and stem brotowali effective pest control armyworms in pepper sauce. The research was carried out experimentally using completely randomized design (CRD) with 6 concentrations of 0 ml/l, 35 ml/l, 40 ml/l, 45 ml/l, 50 ml/l and 55 ml/l, respectively repeated 4 times. The parameters measured were mortality and armyworm feeding activity for 24 hours and observed every 4 hours. Data were analyzed by using Probit Program Version 1.5 continues the analysis of correlation of mortality armyworm larvae. For armyworm feeding activity was analyzed using one-way analysis of variance (ANOVA one-way) and proceed with the Least Significant Difference test (LSD). The results showed that the combination of mahogany seed extract and stem brotowali can cause mortality and a decrease in feeding activity. Effective concentration to control armyworms concentration is 55 ml/l.